Novel steganography scheme using Arabic text features in Holy Quran - Huda Kadhim Tayyeh; Mohammed Salih Mahdi; Ahmed Sabah Ahmed AL-Jumaili (Institute of Advanced Engineering and Science, 2019)
With the rapid growth of the Internet and mobile devices, the need for hidden communications has significantly increased. Steganography is a technique introduced for establishing hidden communication, Most steganography techniques have been applied to audio, images, videos, and text. Many researchers used steganography in Arabic texts to take advantage of adding, editing or changing letters or diacritics, but lead to notable and suspicious text. In this paper, we propose two novel steganography algorithms for Arabic text using the Holy Quran as cover text. The fact that it is forbidden to add, edit or change any letter or diacritics in the Holy Quran provides the valuable feature of its robustness and difficulty as a cover in steganography. The algorithms hide secret messages elements within Arabic letters benefiting from the existence of sun letters (Arabic: ḥurūf shamsīyah) and moon letters (ḥurūf qamarīyah). Also, we consider the existence of some Arabic language characteristics represented as small vowel letters (Arabic Diacritics). Our experiments using the proposed two algorithms demonstrate high capacity for text files. The proposed algorithms are robust against attack since the changes in the cover text are imperceptible, so our contribution offers a more secure algorithm that provides good capacity.